POTENSI PROPOLIS SARANG LEBAH HITAM (Trigona Spp) UNTUK PENYEMBUHAN LUKA BAKAR - Kamayani, Made Oka Ari; Lestari, A.A. Wiradewi; Tirtayasa, Ketut; Mantik Astawa, I Nyoman (Coping: Community of Publishing in Nursing, 2023)
Burns are trauma caused by thermal injury and require continuous care. One of the complications of healing burns is infection, which interferes with the wound healing process.  Propolis has various biological activities, especially anti-inflammatory and bactericidal effects, so it has the potential to be used for healing burns. The aim of this study was to analyze the potential of stingless bee propolis (Trigona spp) for healing burns. The research used a descriptive analytical design, which was carried out in March 2023. Stingless bee propolis was obtained from Banjar Adat Pedukuhan, Rendang Village, Rendang District, Karangasem, Bali. Propolis is formed in the form of Ethanol Propolis Extract (EEP) and is examined quantitatively and qualitatively. Qualitative examination results showed that the content of stingless bee propolis consisted of flavonoids, phenols, tannins, steroids and triterpenoids. The results of the quantitative examination showed that the total flavonoids were 83,62 mg/OE/100 g; total tannin of 1452,88 mg TAE/100 g; total phenol was 1766,89 mg GAE/100 g, and IC50 was 285,86. It can be concluded that stingless bee propolis has potential in healing burns, although the IC50 content shows very weak antioxidant activity. Further gradual research is needed to strengthen the potential of stingless bee propolis in healing burns.